Lipid Peroxidation, Antioxidant Enzymes and Pyruvate Kinase Activity in Rats with Carbon Tetrachloride-Induced Cirrhosis - Yilmaz, Seval; Bahçecio?iu, Ibrahim Halil (My University, 2000)
Changes in the level of malondialdehyde (MDA, a degradative product of lipid peroxidation) and in the antioxidant defense system in rats with carbon tetrachloride-induced liver cirrhosis were studied, in order to determine whether there is any relation between these parameters and the disease. Liver cirrhosis was induced in Wistar-Albino rats by carbon tetrachloride (0.15 gr/100 gr body weight) which was injected subcutanously three times a week for six weeks. In the liver, the level of tissue malondialdehyde was analysed according to Yagi's method; and glutathione peroxidase, glucose-6-phosphate dehydrogenase, pyruvate kinase activities according to Beutler's method. The level of liver malondialdehyde in the group with cirrhosis was significantly higher than in the control group (p<0.05). Glutathione peroxidase and glucose-6-phosphate dehydrogenase activity was significantly lower in the group with cirrhosis than in the control group (p<0.05). The difference was not statistically significant for pyruvate kinase activity (p>0.05). Thus, we consider that cirrhosis causes changes in the antioxidant defense system and it can lead to oxidative stress and peroxidation.
Karbontetraklorür ile Siroz Oluşturulmu? Ratlarda Lipid Peroksidasyonu, Antioksidant Enzim ve Pirüvat Kinaz Aktiviteleri
Keywords: Cirrhosis; Glucose-6-phosphate dehydrogenase; Glutathione peroxidase; Lipid peroxidation; Pyruvate kinase